Pecking order theory in a bank-centered lending environment - Evidence from North European economies - Laisi, Tommi (My University, 2016)
The purpose of this study is to find out whether North European firms follow the pecking order theory in their annual financing decisions. The hypotheses propose that the pecking order behavior is strong but weakens after the financial crisis. The effect of tightening financial regulation and various sub groups of firms are studied separately. North European economies differ from other developed economies in having a bank-centered financing environment which provides a relatively new and interesting environment to study firms’ annual financing decisions. The sample data from 2005 to 2014 consists of all publicly listed Finnish, Swedish, Norwegian, Danish and Icelandic firms with sufficient financial data available. Sufficient financial data enables studying annual financing decisions with various proxies for changes in firm capital structure and on various sub groups of firms. All regressions are adjusted for year and firm fixed effects in order to control for the effects of corporate restructurings and to reduce potential endogeneity problems The results show strong support for pecking order behavior in Nordic firms’ annual financing decisions. Previous studies have found evidence both for and against which implies that time period and market characteristics have an effect on firm financing decisions. Despite studying a variety of sub groups, the evidence is strong for all types of firms in the North European economies. The main implication is that all listed firms in the North Europe behave similarly in terms of their financing decisions. One of the main purposes of this paper is studying the effect of tightening financial regulation. Utilising a dummy variable to study differences between two periods, the results are able to find positive and significant yet only a small difference in firm financing decisions. The results indicate that firms have begun to more diversify their funding after the financial crisis.
Keywords: Pecking order; capital structure; North Europe; financial crisis; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|